A population dynamics approach to understand the invasiveness of the seaweed Rugulopteryx okamurae (Ochrophyta, Dictyotales) - Rosas-Guerrero, Jesús; Carmona-Fernández, Raquel; De la Rosa, Julio; Zanolla-Balbuena, Maríanela Fernanda; Altamirano-Jeschke, María (Pensoft Publishers, 2025)
The success of invasive species can be measured by invasiveness, which depicts intrinsic characteristics that enable them to thrive in new environments. In invasive seaweeds, for example, the persistence of multiple overlapping cohorts throughout the year plays a key role in increasing plant cover and exerting unrelenting pressure on invaded areas. The marine brown macroalgae Rugulopteryx okamurae has recently established abundant populations in the Mediterranean Sea and Atlantic Ocean, negatively affecting both biodiversity and socioeconomic factors by unprecedently aggressive invasive behaviour. The objective of the study is to understand the invasiveness of R. okamurae through its population dynamics. For this, a year-round study was conducted in a protected habitat of Posidonia oceanica in southern Spain, revealing that R. okamurae uses alternating mechanisms for population maintenance. It achieves high density of young individuals in late summer and autumn, peaking at 3285 individuals per square metre. In spring and early summer, the population shifts towards fewer – but larger – individuals, with densities dropping to 888 individuals per square metre and biomass reaching a peak of 170 g dry weight (DW) per square metre. Six overlapping cohorts were identified by Gaussian curves. They persisted throughout the year, but they were not related to environmental factors, which indicates adaptive physiological mechanisms that sustain dense monospecific populations. Additionally, the association between cohorts and different morphotypes suggests that R. okamurae phenotypic plasticity enables its persistence in introduced areas. These findings provide valuable insights into the biological traits underpinning its invasiveness in P. oceanica meadows, revealing temporal windows of invasiveness driven by different mechanisms. This knowledge is crucial for developing effective conservation and management strategies aimed at mitigating the impact of this invasive species.
Keywords: Especies exóticas invasoras; Demography; Density; Generation; Macroalga; Posidonia oceanica; Recruitment